Pharmacogenetics of tardive dyskinesia: a "movement" towards individualized therapy 1 - Basile, Vincenzo (Henry Stewart Talks, 2007)
Postulated mechanisms of schizophrenia, Dopaminergic pathways in schizophrenia, The Pharmacogenetic paradigm, Pharmacokinetic-pharmacodynamic-environmental interactions, Complex trait genetics, Antipsychotic adverse reactions, Tardive dyskinesia, Postulated mechanisms, Genetic association studies of TD, Candidate genes in TD, Pharmacodynamics and TD: a look at dopaminergic and serotonergic candidates
Archived at 2021/02/25